Acidic domains around nucleic acids. - Lamm, G (1990)
The hydrogen ion concentration in the vicinity of DNA was mapped out within the Poisson-Boltzmann approximation. Experimental conditions were modeled by assuming Na-DNA to be solvated in a buffer solution containing 45 mM Tris and 3 mM Mg cations at pH 7.5. Three regions of high H+ concentration (greater than 10 microM) are predicted: one throughout the minor groove of DNA and two localized in the major groove near N7 of guanine and C5 of cytosine for a G.C base pair. These acidic domains correlate well with the observed covalent binding sites of benzo[a]pyrene epoxide (N2 of guanine) and of aflatoxin B1 epoxide (N7 of guanine), chemical carcinogens that presumably undergo acid catalysis to form highly reactive carbocations that ultimately bind to DNA. It is suggested that these regions of high H+ concentration may also be of concern in understanding interactions involving proteins and noncarcinogenic molecules with or near nucleic acids.